2009
DOI: 10.1038/nature08610
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the formate transporter FocA reveals a pentameric aquaporin-like channel

Abstract: FocA is a representative member of the formate-nitrite transporter family, which transports short-chain acids in bacteria, archaea, fungi, algae and parasites. The structure and transport mechanism of the formate-nitrite transporter family remain unknown. Here we report the crystal structure of Escherichia coli FocA at 2.25 A resolution. FocA forms a symmetric pentamer, with each protomer consisting of six transmembrane segments. Despite a lack of sequence homology, the overall structure of the FocA protomer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
221
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(234 citation statements)
references
References 35 publications
11
221
0
2
Order By: Relevance
“…PFC0725c encodes a single putative formate-nitrite transporter (PfFNT, 34.4 kDa) whose expression profile 11,12 parallels that of the plasmodial HT (Fig. 1b), the lactate dehydrogenase and all glycolytic enzymes ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…PFC0725c encodes a single putative formate-nitrite transporter (PfFNT, 34.4 kDa) whose expression profile 11,12 parallels that of the plasmodial HT (Fig. 1b), the lactate dehydrogenase and all glycolytic enzymes ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used the available crystal data of various bacterial FNTs 12,[14][15][16] ( Supplementary Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, recent fi ndings have demonstrated that a formate transporter shows an AQP-like channel structure [34,35] , thus lending support to the radical notion that an aquaporin structure may have the potential to function as a unidirectional water transporter in cooperation with other molecules, at least under certain circumstances.…”
Section: Efficient Sperm Volume Regulation Is a Prerequisite For Normmentioning
confidence: 84%